Car drivers’ preferences for ISA policy measures - Molin, Eric; Bos, Gertjan van den (European Journal of Transport and Infrastructure Research, 2014)
Intelligent Speed Adaptation (ISA), an in-vehicle system that can either warn the driver or directly limit the vehicle’s speed when the speed limit is reached, is generally believed to have a large potential to increase road safety. However, policy makers hesitate to take policy measures that may increase ISA use. Public acceptance of ISA or policy makers’ perception of it is regarded to play an important role in this. This paper aims to increase this insight by reporting car drivers’ preferences for ISA policy measures based on stated choice experiment conducted in the Netherlands. Respondents made choices between various implementation strategies (mandatory ISA and voluntary ISA with financial incentives) given a chosen policy measure. The policy measure describes which drivers group (speed offenders, professional drivers or all drivers) is targeted and which ISA type (warning or limiting) is stimulated. The results point out that car drivers especially prefer that policy makers would impose ISA on speed offenders and to a lesser extent also on professional drivers, while they prefer a voluntary ISA for themselves. Use of voluntary ISA can be stimulated by offering financial incentives, of which purchase subsidy is preferred above annual tax cuts. Furthermore, car drivers prefer warning ISA for themselves and also for professional drivers, while they prefer limiting ISA for speed offenders. In addition, the results indicate that females and the older age group prefer ISA policy measures more than males and young drivers, but overall car drivers’ preferences seem to be rather homogeneous.